Experimental study of mass exchange characteristics of vortex spray mass exchange devices - Ал Хайят, Надим Касим Мохаммед (Eastern-European Journal of Enterprise Technologies, 2014)
During the study, the theoretical bases of the experimental determination of mass exchange characteristics of VSCMED were investigated, stand for this was designed and manufactured. Graphical dependencies, illustrating the change in the target substance concentration under different hydrodynamic regimes were obtained. The study is aimed at optimizing the geometric dimensions of the vortex mass exchange chambers. The conditions for fine-dispersed spraying of liquid in VSCMED that has a positive effect on increasing the mass exchange surface were considered. Based on the data obtained, we recommend maintaining the speed in the entrance slits of at least 24 m/s while gas velocity in the spray zone will be more than 60 m/s. These conditions allow to obtain the mass transfer coefficient more than 0.00085 mol/m3c and minimal geometrical dimensions of the device. As a result, recommendations for designing devices that allow to develop an engineering calculation methodology of the mass exchange characteristics of the absorption process and geometrical dimensions of VSCMED were obtained.